Penyelesaian Sengketa Lingkungan Hidup Melalui Pengadilan - Cut Era Fitriyeni (Universitas Syiah Kuala, 2010)
ABSTRACT: The settlement of the environmental dispute through the court of environmental law might be solved by litigation or non litigation. The settlement of the environmental dispute through the court by claiming based on Article 87 of the Act Number 32, 2009 regarding the Protection and Environmental Control in conjunction with Article 1365 of the Civil Act. It concerns the acts, and/or conducts using the disposal B3 or/and causing the serious threat towards the environment applies absolute strict liability principle. The Environmental Dispute Settlement Through Ligitation